Evaluation of Nigerian agricultural production data - Hatzenbuehler, Patrick L.; Abbott, Philip C.; Abdoulaye, Tahirou (2017)
The absence of an agricultural census in Nigeria means that samples for surveys to estimate agricultural production are obtained from a non-comprehensive, non-representative set of farms. Therefore, aggregate production data quality is questioned. The methods employed herein provide a new way to empirically evaluate the quality of agricultural production estimates. Two objective types of data, namely the normalised difference vegetation index (NDVI), a satellite remote-sensing measure of intertemporal vegetation changes, and prices, which reveal supply-use dynamics, are used to analyse the degree to which agricultural production estimates reflect adjustments in growing/market conditions. Broadly weak relationships were found between the production estimates and these objective measures, but with variations in degree across states. In addition, these two objective measures are more strongly related to each other than either is to production data. The results imply that the inclusion of NDVI and prices in agricultural production estimation models would improve the quality of the Nigerian production estimate.